MSCs seeded on bioengineered scaffolds improve skin wound healing in rats. Issue 1 (26th February 2015) - Formigli, Lucia; Paternostro, Ferdinando; Tani, Alessia; Mirabella, Carlo; Quattrini Li, Alessandro; Nosi, Daniele; D'Asta, Federica; Saccardi, Riccardo; Mazzanti, Benedetta; Lo Russo, Giulia; Zecchi‐Orlandini, Sandra
Abstract Growing evidence has shown the promise of mesenchymal stromal cells (MSCs) for the treatment of cutaneous wound healing. We have previously demonstrated that MSCs seeded on an artificial dermal matrix, Integra (Integra Lifesciences Corp., Plainsboro, NJ) enriched with platelet‐rich plasma (Ematrix) have enhanced proliferative potential in vitro as compared with those cultured on the scaffold alone. In this study, we extended the experimentation by evaluating the efficacy of the MSCs seeded scaffolds in the healing of skin wounds in an animal model in vivo. It was found that the presence of MSCs within the scaffolds greatly ameliorated the quality of regenerated skin, reduced collagen deposition, enhanced reepithelization, increased neo‐angiogenesis, and promoted a greater return of hair follicles and sebaceous glands. The mechanisms involved in these beneficial effects were likely related to the ability of MSCs to release paracrine factors modulating the wound healing response. MSC‐seeded scaffolds, in fact, up‐regulated matrix metalloproteinase 9 expression in the extracellular matrix and enhanced the recruitment of endogenous progenitors during tissue repair. In conclusion, the results of this study provide evidence that the treatment with MSC‐seeded scaffolds of cutaneous wounds contributes to the recreation of a suitable microenvironment for promoting tissue repair/regeneration at the implantation sites.